Case studies on contract dispute under SOP framework - Tan, Yi Xun (2015)
This FYP report serves as a record and study the industry use of legislation application towards the payment of Security of Payment, SOP in the construction sector. Due to a period of payment dispute in the industry, the parliament introduced Building and Construction Industry Security of Payment Act (SOPA) in 2004 to curb the rising problem in the construction industry. An extensive study was done on foreign SOP like Australia, UK and New Zealand for reference and improvement in the local SOP Act. The FYP will also have an overview of cases on common dispute issues between a Subcontractor and Main Contractor. The method of study includes referring to the past three years, actual construction dispute cases in Singapore. Further analysis and details will be described in the FYP report. The Report uses cases like RN & Associates Pte Ltd V TPX Builders Pte Ltd, Chip Hup Hup Kee Construction Pte Ltd V Ssangyaong Engineering & Construction Co Ltd and SEF Construction Pte Ltd Vs Skoy Connected Pte Ltd etc., discuss the relevancy towards the SOP payment dispute and delay in payment response. Focusing on payment response as the main issue in the report scope, payment response issue on the various cases will be further elaborated in comparison with other selected cases. In conclusion, the author has come to a few observations taken place in the concept of SOP. Recommendations are also included to build in as an additional refinement in the SOP.